Enhanced dietary awareness and lifestyle changes in first-year medical students following exposure to problem-based nutrition education - E.M. Peters; S.B. Higgins-Opitz; M. McLean; J. van Wyk (South African Family Practice)
Background: The ever-increasing prevalence of chronic lifestyle-associated diseases has resulted in greater awareness of the importance of preventative medicine and its incorporation as an integral component of modern undergraduate medical curricula. As excessive dietary intake and physical inactivity are widely acknowledged as leading risk factors for the onset of chronic lifestyle-associated diseases, the promotion of a healthy lifestyle is regarded as a priority for today's primary care physicians. For this reason, it was deemed appropriate by the designers of the problem-based learning (PBL) curriculum, which was introduced at the Nelson R. Mandela School of Medicine in 2001, to include a six-week Nutrition theme early in the medical students' five-year curriculum. This study set out to determine the impact of this theme, which included a specific focus on the importance of nutrition in avoiding lifestyle-associated disorders, on the dietary awareness and lifestyle of the 2004 intake of medical students.